Jammu and Kashmir land revenue laws in the era of new governance - Faaz, Zakir Hussain (New Delhi Educational Publication, 2024)
The Jammu and Kashmir land revenue laws have undergone significant changes in the era of new governance, particularly after the 5th August , 2019. These changes are significant shift from the previous laws, where certain protections were in place form permanent residents, especially concerning land ownership and transfer. Latest amendments have been a subject of extensive discussion, analysis and aim to encourage investment and development and potential to reshape the future of Jammu and Kashmir in terms of economy, and social fabric.
Keywords: Land Revenue Laws; Governance